Comparative Analysis of Ferittin Levels and Liver Enzymes Activity in Disease Patients within Benin City - Ebehitale Comfort Inegbenehi,1 Babatunde Ishola Gabriel Adejumo, 1 Moses Ojo Oke2, Fidelis Ohiremen Oyakhire3*, Uche Cletus Odionyenma4, Usman Itakure Abdulkadir5 (Sokoto Journal of Medical Laboratory Science)
Liver disease encompasses a spectrum of hepatic pathologies, ranging from minor disturbances in liver function to severe conditions such as cirrhosis and hepatocellular carcinoma. The aim of this study was to assess the serum concentrations of ferritin and liver enzymes (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) in patients diagnosed with liver disease in Benin City, Edo State. A cohort of eighty-eight (88) individuals, consisting of forty-four (44) subjects diagnosed with various forms of liver disease and forty-four (44) healthy controls devoid of liver pathology history, were recruited. Blood samples were collected via standard venipuncture technique, and subsequent analysis included measurement of ferritin levels using Enzyme Linked Immunosorbent Assay (ELISA) and determination of AST and ALT activities via colorimetric method. Predominantly, male participants accounted for 52.3% of the cohort, with females comprising 47.7%. Elevated levels of AST and ALT were evident in liver disease patients compared to controls, whereas ferritin levels displayed no significant disparity between the control group (112.24±11.92) and liver disease patients (100.03±19.00) (p>0.05). The findings underscore heightened levels of ALT and AST in individuals afflicted with liver disease compared to healthy controls, thus emphasizing the potential utility of these biomarkers in liver disease diagnosis and management.